2014
DOI: 10.1371/journal.pone.0092907
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces alboflavus RPS and Its Novel and High Algicidal Activity against Harmful Algal Bloom Species Phaeocystis globosa

Abstract: Phaeocystis globosa blooms have frequently occurred along coastal waters and exerted serious impacts on ecological environments by releasing toxic hemolytic substances, forming nuisance foam, and causing oxygen depletion. An actinomycete strain RPS with high algicidal activity against P. globosa was isolated and identified as Streptomyces alboflavus, based on morphology, physiological and biochemical characteristics, and 16S rDNA sequence analysis. RPS lysed 95% of P. globosa within 48 h by releasing an extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…Strain AM11 was isolated on PDA medium and cultured in Czapek' solution . Streptococcus enrichment (SE) medium was used to culture host algae (i.e., C. pyrenoidosa ) under white fluorescent light (50 μmol photons m −2 s −1 ) using a light period of 12 hours at 25°C .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain AM11 was isolated on PDA medium and cultured in Czapek' solution . Streptococcus enrichment (SE) medium was used to culture host algae (i.e., C. pyrenoidosa ) under white fluorescent light (50 μmol photons m −2 s −1 ) using a light period of 12 hours at 25°C .…”
Section: Methodsmentioning
confidence: 99%
“…All types of algicidal bacteria may generate various algicide and algicidal mechanisms . Many researchers support the hypothesis that indirectly algicidal bacteria could lyse or kill algae cell mainly through inhibition of the respiratory chain to inhibit synthesis of algae cell wall or spore formation .…”
Section: Introductionmentioning
confidence: 99%
“…To test for algicidal activity, A. tamarense was inoculated into a 24-well cell plate, and the fluorescence intensity (RFU) of algae in each well was measured at an excitation wavelength of 440 nm and emission wavelength of 680 nm (Spectra max M2, Molecular Devices Corporation) and the result treated as algal biomass [34]. One red colored strain was isolated, which showed high algicidal activity, and this strain was designated Y35.…”
Section: Isolation Of Algicidal Strainmentioning
confidence: 99%
“…Considerable efforts have been devoted to the investigation of environmental conditions that regulate the occurrence and maintenance of P. donghaiense blooms and the cellular responses of this dinoflagellate to different conditions, such as N/P repletion, N/P depletion, different N/P substrates, acidification, and eutrophication (25)(26)(27)(28)(29). Although many algicidal bacteria have been identified and exploited in the control of Microcystis aeruginosa (5,7,14,17,30), Alexandrium tamarense (9,12,18,19), Phaeocystis globosa (8,11,16,(31)(32)(33), and Skeletonema costatum (34)(35)(36)(37), few studies have reported bacteria with algicidal effects against P. donghaiense. Therefore, an effective biocontrol method for the prevention and dissolution of P. donghaiense algal blooms must be developed.…”
mentioning
confidence: 99%